Doses de nitrogênio aplicados na cultura da soja, com e sem inoculação - Parizzi, Felipe Bennemann (2022)
The objective of this work was to verify the effect of different doses of N on soybean, work carried out in the 2021/2022 crop, in a commercial area of a private property located on the PARIZZI farm, in the municipality of Ipiranga do Norte, MT. The experimental design was in randomized blocks with a 2 x 5 factorial scheme, consisting of 5 doses of environment 0 (control); 10, 20, 30, 30, 40 kg ha-1 and applied in seedlings treated with and without inoculation with bactericides, as inoculum, as a source of nitrogen (N) (45% of N) applied at the V4 stage of culture, with dose of 100 ml 1 kg-1 of seeds, were applied in the seed treatment before sowing, the soybean sown was a commercial cultivar 83HO113 TP IPRO. as variables of areas of pods, pods, mass of cultivation, weight for crops, root grains of productivity increase, productivity if the weight of culture, varieties of roots of productivity increase, productivity if the weight cultivation, varieties of growing roots and yielding that the fertilization of the crop of the combination with nitrogen produces yield even in the highest doses (40 kg ha-1). The stem diameter, leaf area, plant height, weight of a thousand seeds and number of pods benefit from nitrogen fertilization in doses of up to 40 kg ha-1.